An Inventory of Anthelmintic Plants across the Globe - Ahmed, Haroon; Kilinc, Seyma Gunyakti; Celik, Figen; Kesik, Harun Kaya; Simsek, Sami; Ahmad, Khawaja Shafique; Cao, Jianping (Mdpi, 2023)
A wide range of novelties and significant developments in the field of veterinary science to treat helminth parasites by using natural plant products have been assessed in recent years. To the best of our knowledge, to date, there has not been such a comprehensive review of 19 years of articles on the anthelmintic potential of plants against various types of helminths in different parts of the world. Therefore, the present study reviews the available information on a large number of medicinal plants and their pharmacological effects, which may facilitate the development of an effective management strategy against helminth parasites. An electronic search in four major databases (PubMed, Scopus, Web of Science, and Google Scholar) was performed for articles published between January 2003 and April 2022. Information about plant species, local name, family, distribution, plant tissue used, and target parasite species was tabulated. All relevant studies meeting the inclusion criteria were assessed, and 118 research articles were included. In total, 259 plant species were reviewed as a potential source of anthelmintic drugs. These plants can be used as a source of natural drugs to treat helminth infections in animals, and their use would potentially reduce economic losses and improve livestock production.
Keywords: ethnomedicine; anthelmintic; medicinal plant; helminth; global distribution